CXCL9 and CXCL10 display an age-dependent profile in Chagas patients: a cohort study of aging in Bambui, Brazil - Fernanda Fortes de Araújo; Karen Cecília Lima Torres; Sérgio Viana Peixoto; Antonio Luiz Pinho Ribeiro; Juliana Vaz Melo Mambrini; Vitor Bortolo Rezende; Maria Luiza Lima Silva; Antônio Ignácio Loyola Filho; Andréa Teixeira-Carvalho; Maria Fernanda Lima-Costa; Olindo Assis Martins-Filho (BMC, 2020)
Abstract Background Chagas disease is endemic in Latin America and still represents an important public health problem in the region. Chronic cardiomyopathy is the most significant chronic form due to its association with morbidity and mortality. The last decade has seen increasing evidence that inflammatory cytokines and chemokines are responsible for the generation of inflammatory infiltrate and tissue damage, with chronic chagasic cardiomyopathy patients presenting a pro-inflammatory immune response. Although studies have evaluated the role of chemokines in experimental T. cruzi infection, few have addressed their systemic profile, especially for human infection and in aging populations. The present work aimed to use the data from a large population based study of older adults, conducted in an endemic area for Chagas disease, to examine the association between serum levels of cytokines and chemokines, T. cruzi infection and electrocardiogram (ECG) abnormality. Methods The present work evaluated serum levels of CCL2, CXCL9, CXCL10, CCL5, CXCL8, IL-1β, IL-6, TNF, IL-12 and IL-10 by Flow Cytometric Bead Array assay (CBA) and the results expressed in pg/ml. The baseline survey started in January 1st 1997, with 1284 participants of an aged population-based cohort. Participants signed an informed consent at baseline and at each subsequent visit and authorized death certificate and medical records verification. Results Our results demonstrated that Chagas disease patients had higher serum levels of CXCL9, CXCL10 and IL-1β and lower serum levels of CCL5 than non-infected subjects. Moreover, our data demonstrated that CXCL9 and CXCL10 increased in an age-dependent profile in Chagas disease patients. Conclusion Together, this study provided evidences that serum biomarkers increase along the age continuum and may have potential implications for establishing clinical management protocols and therapeutic intervention in Chagas disease patients.